Pre‐operative and intra‐operative chemical thromboprophylaxis increases bleeding risk following elective cholecystectomy: a multicentre (PROTECTinG) study. Issue 12 (9th June 2020) - Liu, David S.; Stevens, Sean; Wong, Enoch; Fong, Jonathan; Mori, Krinal; Ward, Salena; Lee, Sharon; Howard, Tess; Jain, Anshini; Gill, Anna S.; Beh, Pith S.; Slevin, Maeve; et al.
Abstract : PROTECTinG (Perioperative Timing of Elective Chemical Thromboprophylaxis in General surgery) is a multicentre cohort study which has demonstrated that perioperative chemical thromboprophylaxis usage is variable among patients undergoing elective cholecystectomy. The rate of clinical venous thromboembolism post‐cholecystectomy is low. Early chemoprophylaxis increases bleeding risk without an appreciable additional protection from venous thromboembolism. Abstract: Background: Cholecystectomy is commonly performed in general surgery. Despite guidelines recommending chemical thromboprophylaxis in the perioperative period, the most appropriate time for its initiation is unknown. Here, we investigated whether timing of chemoprophylaxis affected venous thromboembolism (VTE) and bleeding rates post‐cholecystectomy. Methods: Retrospective review of all elective cholecystectomies performed between 1 January 2018 and 30 June 2019, across seven Victorian hospitals. Clinical VTE was defined as imaging‐proven symptomatic disease within 30 days of surgery. Major bleeding was defined as the need for blood transfusion, surgical intervention or >20 g/L fall in haemoglobin from baseline. Results: A total of 1744 cases were reviewed. Chemoprophylaxis was given early (pre‐ or intra‐operatively), post‐operatively or not given in 847 (48.6%), 573 (32.9%) and 324 (18.6%) patients, respectively. This varied significantly between surgeons, fellows, trainees and institutions. Clinical VTE occurred in 5 (0.3%) patients and was not associated with chemoprophylaxis timing. Bleeding occurred in 42 (2.4%) patients. Of this, half were major events, requiring surgical control in 5 (11.9%) patients and blood transfusion in 9 (21.4%) patients. Bleeding also extended length of stay (mean (SD), 3.1 (4.0) versus 1.4 (2.2) days, P < 0.001). One bleeding‐related mortality was recorded. Importantly, when compared with post‐operative (risk ratio 1.46, 95% confidence interval 1.21–1.62) and no (RR 1.23, 95% CI 1.03–1.35) chemoprophylaxis, early usage significantly increased bleeding risk and independently predicted its occurrence. Conclusions: Perioperative chemoprophylaxis is variable among patients undergoing elective cholecystectomy. The rate of clinical VTE post‐cholecystectomy is low. Early chemoprophylaxis increases bleeding risk without an appreciable additional protection from VTE.